Do clinical and psychosocial factors affect health-related quality of life in adolescents with chronic diseases? - Santos, Teresa (2019)
Copyright © 2006 - 2018 The Canadian Center of Science and Education. All Rights Reserved. Copyright for this article is retained by the author(s), with first publication rights granted to the journal. This is an open-access article distributed under the terms and conditions of the Creative Commons Attribution license (http://creativecommons.org/licenses/by/4.0/).